(untitled) (Proceedings of the Global Public Health Conference, 2023)
Background: The condition of eating difficulties in children can cause disruption to the growth and development of children. One study in 2015 in the Kedungmundu district stated that most malnourished children had eating difficulty. Factors that influence it include organic factors related to medical conditions, and non-organic factors related to diet, breastfeeding behavior, and parental factors. This study aims to determine the relationship between breastfeeding behavior, maternal emotional factors, the application of basic feeding rules (BFR), culture in applying BFR to children’s eating difficulties. Methods: This study used mixed method with a cross sectional design. The study was conducted in the Kedungmundu district, Semarang City, Indonesia, in October 2022. The research subjects were taken by consecutive sampling as many as 55 subjects. Eating difficulty, implementation of BFR, cultural in implementing BFR, and maternal emotional factors were assessed using a questionnaire that had been through previous validity and reliability tests. Test analysis was carried out by using Mann Whitney and Chi Square. Results: The majority of children had eating difficulty (87.3%), female (54.2%), breastfed for 2 years (93.8%), exclusively breastfed (64.6%), had direct breastfeeding method (66.7%), mother’s emotional state isn’t good (58.3%), applies the BFR for child’s diet (79.2%), and had culture that supports the implementation of the BFR (93.8%). There is a significant relationship (p=0,018) between duration of breastfeeding and eating difficulties. Children also tend to get bored with monotonous food. Conclusion: Factor that influence the incidence of eating difficulties in children aged 24-36 months are the duration of breastfeeding. Food variations also affect children’s appetite which causes children to have eating difficulty.